Nicht Wissen ist auch Macht: zur Gesprächsdynamik der Eingangsszene in Platons Kratylos - Winter, Kathrin (Philologus, 2021)
In the introductory scene of Plato’s Cratylus a power game takes place that is based on an asymmetrical distribution of knowledge and which determines the dynamics of the communication. Since Cratylus claims to have greater knowledge than Hermogenes, he puts his discussion partner in an inferior position. Hermogenes strives to balance out this power differential by different strategies. One such strategy is that of including Socrates in the discussion. Socrates reacts to the power differential that Cratylus has built up in a different way from Hermogenes: by the fact that he claims no knowledge for himself but even rejects any knowledge, he succeeds in gaining a position superior to Cratylus and Hermogenes.
Gesehen am 28.06.2022